Impact of aging on curative health care workforce: Country report Poland - Stanisława Golinowska; Ewa Kocot; Agnieszka Sowa (Center for Social and Economic Research (CASE), 2014)
The report discusses employment in the health care system in Poland based on analysis and projections of the demand and supply of medical workforce. The impact of the financial situation and policy on relativelly low employment level of medical personel was accounted for in the analysis while projections were driven by demographic changes in the following two decades. Results of different demographic variants of projections used in Neujobs project and additional scenarios show that while ageing is an important factor that may stimulate demand for provision of medical personnel, changes might be mitigated by further increase in efficiency of care. At the same time the supply of care will be affected by ageing too. The results indicate that more detailed monitoring of employment in the future will be needed in order to assure adequacy of provision of medical professionals, especially of nurses (critical gap), some medical specialists, physiotherapists and medical technical personnel.
Keywords: H51; H75; I18; 330; Health Care; Employment in Health Care; Employment Projections; Labor Resources in Health; Medical Professions